2019
DOI: 10.3390/ani9020032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Stevioside Supplementation on Feed Intake, Digestion, Ruminal Fermentation, and Blood Metabolites of Goats

Abstract: The objective of this study was to evaluate the effects of dietary inclusion of tevioside on feed intake, feeding behavior, nutrient digestion, rumen fermentation, and serum biochemical parameters in goats. Nine male Xiangdong black goats (21.8 ± 1.5 kg of body weight) were used in a replicated 3 × 3 Latin square. All goats were fed a basal diet including concentrate and forage (chopped rice traw). The three treatments were 0, 400, or 800 mg stevioside per kg chopped rice traw on a dry matter (DM) basis. Dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…In contrast, stevioside derivatives can stimulate the taste receptors (TASIR2/TASIR3) [ 39 , 40 ] and K + channels in pancreatic β-cells [ 41 ], which can increase the stimulation of appetite and voluntary FI. Similar to the present findings, Han et al 2019 [ 42 ] reported a linear increase in FI in goats given diets supplemented with 270 and 541 mg/kg stevioside. In contrast, Cho et al [ 43 ] reported that the dietary intake of Hanwoo steers is not influenced by the inclusion of 65 mg/kg stevioside as an essential oil to the feed with 0.1% of diet supplemented rate.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, stevioside derivatives can stimulate the taste receptors (TASIR2/TASIR3) [ 39 , 40 ] and K + channels in pancreatic β-cells [ 41 ], which can increase the stimulation of appetite and voluntary FI. Similar to the present findings, Han et al 2019 [ 42 ] reported a linear increase in FI in goats given diets supplemented with 270 and 541 mg/kg stevioside. In contrast, Cho et al [ 43 ] reported that the dietary intake of Hanwoo steers is not influenced by the inclusion of 65 mg/kg stevioside as an essential oil to the feed with 0.1% of diet supplemented rate.…”
Section: Discussionsupporting
confidence: 91%
“…Sweet taste is also correlated with feed intake. A large number of studies have shown that dietary supplementation with sweeteners could promote the feed intake and thereby improve growth performance in livestock, including piglets ( Sterk et al., 2008 , Zhang et al., 2019 ), cattle ( McMeniman et al., 2006 ), and goat ( Han et al., 2019 ). Nevertheless, data are lacking about the impact of dietary supplementation with sweeteners on the feed intake and body weight ( BW ) gain of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that supplementation with steviol glycoside could increase the feed intake of guinea pigs 21 . Dietary STE supplementation is able to increase the palatability of rice straw and thereby promotes the feed intake of goats 22 . Nevertheless, owing to the lack of taste receptor family 1 member 2, chickens are insensitive to sweet substances 3 .…”
Section: Discussionmentioning
confidence: 99%